2013
DOI: 10.1002/hep.25877
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological relevance of neutrophils in acetaminophen hepatotoxicity

Abstract: enzymatic cycling method to detect LPA used in their study is very different from the enzyme-linked immunosorbent assay (ELISA)-based method used in our study. With regard to our data on LPA levels in healthy donors, we effectively detected serum levels 10-fold those detected in plasma. Nevertheless, the values of undiluted human serum samples are perfectly in line with the values reported in the datasheet provided by the manufacturer of the LPA assay kit (Echelon Biosciences) that we used in our study. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Neutrophils and macrophages are two cell types known to express integrin α M β 2 and accumulate in the injured liver after APAP overdose [11, 29, 31, 32]. Hepatic neutrophil accumulation after APAP administration was similar in wild-type and Fibγ 390-396A mice (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Neutrophils and macrophages are two cell types known to express integrin α M β 2 and accumulate in the injured liver after APAP overdose [11, 29, 31, 32]. Hepatic neutrophil accumulation after APAP administration was similar in wild-type and Fibγ 390-396A mice (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…A few studies that have used neutropenia-inducing antibodies have provided evidence for the involvement of neutrophils in the late-stage injury process (Ishida et al, 2006; Liu et al, 2006; Marques et al, 2012). However, this particular approach has been repeatedly criticized for potential off target effects (Jaeschke and Liu, 2007; Jaeschke et al, 2013). On the other hand, a substantial number of other studies using a wide variety of approaches to inhibit neutrophil function have not found any evidence for a neutrophil-induced injury phase (Connolly et al, 2012; Cover et al, 2006; Hou et al, 2012; James et al, 2003; Lawson et al, 2000; Williams et al, 2010a, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…A neutropenia-inducing antibody results in protection against APAP toxicity but only if given 24 h prior to APAP, [41][42][43] but not if given after APAP overdose despite functional inactivation of neutrophils. [44][45][46] Also, neutrophils show no enhanced activation status during the APAP-induced injury phase, 47 priming and activating neutrophils during APAP overdose by IL-1β or endotoxin does not increase injury, 47,48 CD18- 47 and ICAM-1-deficient mice 44 are not protected, an anti-CD 18 antibody did not affect injury, 49 and mice that have inhibited NADPH oxidase or lack NADPH oxidase ( phagocytic respiratory burst) have no difference in oxidant stress or APAP-induced injury. 44,50 Often times neutrophils are thought to be the cause of enhanced injury because in genetic or pharmacologic interventions mice with reduced injury will have lower hepatic neutrophil counts or reduced myeloperoxidase staining, 43,51 however, this is most like due to the fact that mice with less injury, release less DAMPs, and therefore recruit fewer neutrophils.…”
Section: Neutrophilsmentioning
confidence: 99%